2010
DOI: 10.1007/s11274-010-0389-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening for alkaline keratinolytic activity in fungi isolated from soils of the biosphere reserve “Parque Costero del Sur” (Argentina)

Abstract: A screening was carried out on 69 fungal strains isolated from alkaline-calcareous, neutral and alkaline-sodic soils, as well as from their associated plant material, to determine their ability to grow at alkaline pH. A total of 32 fungi were selected for their ability to produce alkaline keratinase activity in submerged shaken cultures supplemented with soybean meal (SM) and tryptone and on cow hair (CH) under solid state fermentation conditions. Although several fungal strains produced keratinolytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…After 42 days of cultivation A. fulvescens strains and Chrysosporium articulatum strain caused solubilisation and mineralization of feather proteins as indicated by the release of peptides and the accumulation of N-NH 4 + in the medium correlated with increased pH reaching 8.6–9.1 (alkalinization). As reported by Sanyal et al (1985) and Elíades et al (2010), an alkaline reaction is favourable for the production of keratinolytic protease by fungi. Korniłłowicz-Kowalska (1997a) demonstrated that saprotrophic keratinolytic fungi, represented mainly by a variety of species of geophilic dermatophytes and Chrysosporium , converted up to 75% of nitrogen into the ammonium form during full solubilization of native feather keratin.…”
Section: Discussionmentioning
confidence: 69%
“…After 42 days of cultivation A. fulvescens strains and Chrysosporium articulatum strain caused solubilisation and mineralization of feather proteins as indicated by the release of peptides and the accumulation of N-NH 4 + in the medium correlated with increased pH reaching 8.6–9.1 (alkalinization). As reported by Sanyal et al (1985) and Elíades et al (2010), an alkaline reaction is favourable for the production of keratinolytic protease by fungi. Korniłłowicz-Kowalska (1997a) demonstrated that saprotrophic keratinolytic fungi, represented mainly by a variety of species of geophilic dermatophytes and Chrysosporium , converted up to 75% of nitrogen into the ammonium form during full solubilization of native feather keratin.…”
Section: Discussionmentioning
confidence: 69%
“…All the fungi isolated were inoculated according to Saparrat and Guillen [32] in a liquid soya-meal medium as reported by Elíades et al [22], and supplemented with buffer-solutions according to Nagai et al [33] to adjust the pH to 9.0. Three replicates for each fungus were incubated for 15 d at 28 ± 1.5 °C under shaking (200 rpm).…”
Section: Microtiter-schreening For α-L-rhamnosidase and β-D-glucosidamentioning
confidence: 99%
“…Twenty-three fungi from the screening were grown on the soya-meal liquid medium at pH 9.0 (basal medium) [22] and in the presence of naringin (Sigma, USA, with purity higher than 99.5% purity). A stock solution of 1 mM of this glucoside in Tris-HCl 20 mM was sterilized by filtration through 0.2 μm cellulose filters and added to the basal medium before inoculating each fungus as reported by Saparrat et al [6].…”
Section: Effect Of Naringin On the Enzyme Production By Selected Fungimentioning
confidence: 99%
See 2 more Smart Citations